2002
DOI: 10.1007/s00216-002-1498-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of proteins at nanogram levels by their quenching effect on the chemiluminscence reaction between luminol and hydrogen peroxide with manganese-tetrasulfonatophthalocyanine as a new catalyst

Abstract: The manganese-tetrasulfonatophthalocyanine (MnTSPc) catalyzed luminol-hydrogen peroxide chemiluminescence (CL) systems can be quenched in the presence of proteins. A highly sensitive CL quenching method has been developed for the determination of proteins. Under optimum conditions, the linear ranges of the calibration curves were 0.1-20 microg/mL for human serum albumin (HSA), 0.2-20 microg/mL for human gamma-IgG, and 0.5-50 microg/mL for the bovine serum albumin (BSA) with the corresponding detection limits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Finally, to benchmark the method, three individual human serum samples were assessed for total protein content using this RLS method. The values obtained had excellent agreement with values arrived at using the more conventional Bradford assay [58].…”
Section: Discrete Qds Coated In Polymers Generated In Situsupporting
confidence: 72%
“…Finally, to benchmark the method, three individual human serum samples were assessed for total protein content using this RLS method. The values obtained had excellent agreement with values arrived at using the more conventional Bradford assay [58].…”
Section: Discrete Qds Coated In Polymers Generated In Situsupporting
confidence: 72%
“…It was reported that some metalloporphyrins such as hemin have strong catalytic activity on luminol-H 2 O 2 CL reaction. 44 The molecular structures of the metalloporphyrins affect their catalytic activity, including their coordination center metal ions and the exterior porphyrin structure such as the carboxyl group, electronegativity, conjugated system, and their steric hindrance. Metalloporphyrin-polymer dots were prepared by using nanoprecipitation, and their catalytic CL activities to the L012-H 2 O 2 reaction were systematically investigated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2, curve b), which means that the process of hydrogen peroxide transferring into intermediate species can be accelerated in the presence of CoTSPc (23,24). On the other hand, when rutin was added into this luminol CL system (Fig.…”
Section: Inhibitive Effect Of Rutin On the Cotspc-catalyzed Luminol Cmentioning
confidence: 95%
“…In 1990, Hara et al first developed the application of metallophthalocyanine compounds as catalysts in the CL reaction between luminol and hydrogen peroxide, and furthermore as labeling reagents in CL immunoassay (22). Metallophthalocyanine has also been used for a wide range of applications in CL analysis (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%